Influence of Marketing Mix Mediated by Customer Satisfaction on Repurchase Intention (Case Study: Fundemi Coffee and Eatery) - Jessica Nathaline Setyo; Lina Salim (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to examine the effect of the marketing mix, which includes product quality, price, place, promotion, and service quality (Servqual), on repurchase intention, with customer satisfaction as a mediating variable. The research was conducted at Fundemi Coffee and Eatery (FCE) Depok, with FCE customers as the study subjects. The sampling method used was probability sampling, with a total sample of 120 respondents. Data was collected through a questionnaire distributed via Google Forms. The analysis method in this study employed the Structural Equation Model (SEM) using Partial Least Squares (PLS). The results of this study indicate that product quality, price, place, and service quality significantly influence repurchase intention, while promotion does not affect repurchase intention. Customer satisfaction successfully mediates the relationship between product quality, place, and service quality on repurchase intention. However, customer satisfaction does not mediate the relationship between price and promotion on repurchase intention.